Structural and Electrical Characterization of Lasral1−Xmgxo4−Δ Layered Perovskites Obtained by Mechanical Synthesis - Serafini, D; Marino-Velasquez, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This work presents the structural and electrical characterization of K2NiF4-type layered perovskites of LaSrAl1−xMgxO4−δ composition to be used as oxide–ion electrolytes for a solid-oxide fuel cell (SOFC). These perovskites were prepared by mechano-chemical synthesis (ball milling), an alternative to traditional synthesis methods such as citrate-nitrates and solid-state reaction. With these methods, two things are avoided: first, the use of nitrate salts, which are more environmentally harmful than oxide precursors, and second, it saves the series of long thermal treatments associated with solid-state reactions. After grinding the precursors, nanometric particles were obtained with a combination of crystalline regions and amorphous regions; this effect was determined by XRD and TEM, showing that Mg has a positive effect on the phase formation by only mechanical synthesis. R2C4: After sintering, it was found by XRD that the sample x = 0.1 only presents the diffraction peaks corresponding to the desired phase, which shows a phase purity greater than 97%, even higher than that of the standard undoped sample. For x = 0.2 and 0.3, there was a segregation of impurities, possibly by the local migration of La and Sr heavy cations; this was determined by SEM and EDS. The electrical characterization of the sintered pellets was carried out by electrochemical impedance spectroscopy, which determined that the incorporation of Mg in the structure improves the ionic conductivity by three orders of magnitude, obtaining conductivities of 1.6 mS/cm at 900 °C for x = 0.2. Although the improvement in conductivity is considerable, many challenges such as densification, the segregation of impurities, and the study of mechanical and thermal properties must be carried out on these materials to endorse them as solid electrolytes in SOFC. © 2023 by the authors.